2017
DOI: 10.18632/oncotarget.17851
|View full text |Cite
|
Sign up to set email alerts
|

An immunocompetent mouse model of human glioblastoma

Abstract: Orthotopic xenotransplantation studies represent the final stage in preclinical cancer research and could facilitate the implementation of precision medicine. To date, these xenografts have been tested in immunodeficient animals, but complete elimination of the adaptive immunity is a significant drawback. We present a method of efficient human glioblastoma (GBM) cell engraftment in adult mice with intact immune systems, mediated by a transient blockade of T-cell co-stimulation. Compared to transplants grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…However, the number of intact breast cancer cells was dramatically reduced after 5 days, although we could still detect isolated DsRed-positive cells and punctate acellular DsRed fluorescence at the lesion site at the end of the experiment. This rapid clearance of the tumour cells may reflect, in part, a graft versus host immune response to the xenotransplantation of a human breast cancer cell line into an immunocompetent mouse [51], although there was very limited infiltration of CD45 hi immune cells at the lesion site. An alternative possibility is that the DsRed cells rapidly die by necrosis or apoptosis, although the significant disruption to the local architecture of the cortical parenchyma in the presence of the cancer cells would argue against this.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of intact breast cancer cells was dramatically reduced after 5 days, although we could still detect isolated DsRed-positive cells and punctate acellular DsRed fluorescence at the lesion site at the end of the experiment. This rapid clearance of the tumour cells may reflect, in part, a graft versus host immune response to the xenotransplantation of a human breast cancer cell line into an immunocompetent mouse [51], although there was very limited infiltration of CD45 hi immune cells at the lesion site. An alternative possibility is that the DsRed cells rapidly die by necrosis or apoptosis, although the significant disruption to the local architecture of the cortical parenchyma in the presence of the cancer cells would argue against this.…”
Section: Discussionmentioning
confidence: 99%
“…This is highly significant as it allows studying behavior of human cells in various available transgenic mouse models or disease systems where adaptive immunity plays important role such as stroke or multiple sclerosis. We have recently shown that similar strategy with CoB can be used for modeling F o r P e e r R e v i e w human glioblastoma in immunocompetent mice (Semenkow et al, 2017) further demonstrating universal utility of this method.…”
Section: Costimulation Blockade-protected Allogeneic Grps Myelinate Amentioning
confidence: 93%
“…The novel gene editing technology CRISPR-Cas9 could also be applied for the development of humanized mice models by substitute part of the mouse gene with a particular gene of human origin to express functional components of the human immune system [ 90 ], such as PD-1/PD-L1, thus enabling the testing of some immune-targeting agents. Instead of constructing murine models with intact human immune systems, some studies have reported their success in generating xenograft models by transplanting human tumor cell lines into immunosuppressed or immunotolerant mice to construct xenografts with intact murine immune systems [ 91 , 92 ]. Using this approach to establish immunocompetent PDX models may be a promising strategy to optimize current immunodeficient models.…”
Section: Future Perspectivesmentioning
confidence: 99%